Review of the genus Tricheops Newman (Coleoptera: Cerambycidae: Cerambycinae) with description of two new species from Western Australia - Evans, Brenda; Ślipiński, Adam (Zootaxa, 2016)
Two new species of Tricheops Newman, T. remus sp. nov. and T. guillemeti sp. nov. from Western Australia are described and illustrated. The genus Tricheops is redescribed and a key to species is provided. The structures associated with the unusual three-lobed eyes of Tricheops and Bardistus Newman are discussed.